Identification of Base Transceiver Station Device Health Using Fuzzy Multi Criteria Decision Making Method on Telkomsel Site - Hamsar , Ali; Maulana , Fajar; Hendra , Yomei (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
The condition of the Base Transceiver Station (BTS) equipment plays an important role in supporting telecommunications services. One of the many complaints from the public about the quality of Telkomsel's network is that it is caused by an unhealthy condition of BTS equipment.In this issue, the aim is to provide information to the Engineer about the health conditions of Telkomsel's BTS devices.The number of BTS identified in this study was 20 BTS in Rokanhulu, Riau. In identifying the health of BTS devices using the Fuzzy Multi Criteria decision making method (FMCDM).The results of the identification of this BTS device in the form of a Dashboard display that becomes the Engineer's information source in determining their work priorities.It can be concluded in this study, the results of the study can help the Telkomsel Engineer to determine the health condition of Telkomsel BTS devices.